2021
DOI: 10.3390/genes12060824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selection Signatures between Korean Native and Commercial Chickens Using 600K SNP Array Data

Abstract: Korean native chickens (KNCs) comprise an indigenous chicken breed of South Korea that was restored through a government project in the 1990s. The KNC population has not been developed well and has mostly been used to maintain purebred populations in the government research institution. We investigated the genetic features of the KNC population in a selection signal study for the efficient improvement of this breed. We used 600K single nucleotide polymorphism data sampled from 191 KNCs (NG, 38; NL, 29; NR, 52;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
(49 reference statements)
0
8
0
1
Order By: Relevance
“…These local breeds have been mainly raised as backyard chickens and are, thus, more resistant to diseases and viruses than commercial chickens, for which selective breeding has reduced resistance to infectious diseases [ 34 ]. In fact, to adapt to these backyard conditions, selective sweeps might have occurred in genomic regions that are related to immune responses and disease sensitivity [ 35 ]. Effects of the geographical area of origin on genomic regions that have been subjected to selection have also been reported in local Italian goats [ 36 ] and sheep [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These local breeds have been mainly raised as backyard chickens and are, thus, more resistant to diseases and viruses than commercial chickens, for which selective breeding has reduced resistance to infectious diseases [ 34 ]. In fact, to adapt to these backyard conditions, selective sweeps might have occurred in genomic regions that are related to immune responses and disease sensitivity [ 35 ]. Effects of the geographical area of origin on genomic regions that have been subjected to selection have also been reported in local Italian goats [ 36 ] and sheep [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genomic studies of local chicken populations worldwide have allowed the identification of signatures of selection in local breeds, using methods based either on an excess of haplotype homozygosity or deformation of the allele frequency spectrum e.g., [ 8 , 9 , 11 , 35 , 41 ]. One observation that has emerged from this study is that, in most cases, the signatures of selection detected in local chicken breeds do not overlap across studies and even between lines from the same geographical location within the same study e.g., [ 35 ]. This is mainly explained by the fact that, following their expansion through human migrations, founder populations of present-day local chicken breeds have experienced drastic bottlenecks [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most interesting gene related to the development of tissues in this region is double PHD fingers 3 ( DPF3 ), which has a role in heart development. The DPF3 gene is specifically expressed during heart development in mice, chickens, and zebrafish, and the knockdown of DPF3 in zebrafish resulted in myocardial contractility and incomplete heart formation; thus, DPF3 was categorized as a major gene for heart development, but it is also involved in skeletal muscle [ 68 , 75 ]. Another important gene related to dwarfism and growth is IGF1R , which was annotated with upstream genetic variation in the MM and MUG analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in Biological Sciences Research, volume 19600K SNP chip data, determined the haplotypes, and directed the selection signals. The conclusion of the study suggested improving the traits related to egg and meat production in NL (KNC black line) and NW (KNC white line) lines respectively and multiple traits in other lines[13].…”
mentioning
confidence: 90%